Distributed management: implementation issues - Lopes, Rui Pedro (2000)
Management processes have to react on time to the new challenges put by a crescent movement of the computing world to the Internet paradigm. The enormous base of legacy knowledge and legacy systems leads the SNMP management framework to a necessary choice in nowadays management scenarios. However, even with the recent SNMPv3, its services correspond roughly to low-level operations for setting or retrieving network equipment parameters. The IETF Distributed Management working group have been producing normalization documents that intent to apply to the enrichment of SNMP semantics, especially in what concerns the processing of management information. This paper will present the recent outcome of this WG and will discuss an implementation project that aims to apply mobile agent technology in these scenarios.